OSCEs for the Primary FRCA - Fox, Joanna Oram; Singh-Kandola, Kiran (Scion Publishing Ltd., 2018)
Candidates sitting the Primary OSCE of the Fellowship of the Royal College of Anaesthetists exams will benefit from the 5 sample full exams contained in this book. Model answers are included, which closely follow the structure and format of the actual exam itself. Printed in full colour throughout